PSIKOEDUKASI BERBASIS VISUALISASI PENGETAHUAN KEKERASAN TERHADAP PEREMPUAN DAN ANAK - Irdianti; Andi Ramdan Al Qadri; Andi Sopy Awaluddin; Sahrullah; Rusnia Ince Mahmuda; A. Nurfadiyah Arkam (Bajang Institute, 2022)
The phenomenon of women violence and child abuse are an issue that has been discussed recently and has become a global public problem that has effects on the condition of victims including for the city of Bulukumba. The number of participants in this psychoeducation are 101 villagers in sub-districts Bulukumpa and Herlang. The method use are giving infographics containing material about violence and pre-post test design to measure understanding of villagers. The result indicates none villagers were in the low category, 10 villagers were in the moderate, and 91 villagers were high category. That it seems the villagers understanding outcomes improved after psychoeducation from the result that the number of villagers in low and moderate category become hi